2016
DOI: 10.1111/jgs.13955
|View full text |Cite
|
Sign up to set email alerts
|

Global Sensory Impairment in Older Adults in the United States

Abstract: Objectives Age-related decline of the five classical senses (vision, smell, hearing, touch, and taste) poses significant burdens on older adults. The co-occurrence of multiple sensory deficits in older adults is not well characterized and may reflect a common mechanism resulting in global sensory impairment. Design, Setting, and Participants The National Social Life, Health, and Aging Project, a representative, population-based study of community dwelling older US adults (57-85 years of age), collected bioma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
112
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 126 publications
(121 citation statements)
references
References 45 publications
(90 reference statements)
6
112
2
1
Order By: Relevance
“…Thus, it is likely that these results are conservative. There may be similar imprecision in other sensory measures, but it is unlikely that these would substantially alter the main results …”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Thus, it is likely that these results are conservative. There may be similar imprecision in other sensory measures, but it is unlikely that these would substantially alter the main results …”
Section: Discussionmentioning
confidence: 95%
“…To address this gap, the concept of global sensory impairment (GSI), which captures common mechanisms underlying decline of the classical senses, was proposed and tested . This model showed that a common underlying factor explained a significant amount of variation in each of the sensory dysfunctions, supporting the concept of a unified underlying process of sensory aging.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Most previous studies were only conducted among older adults 810 12 14 15 Moreover, it has demonstrated that chemosensory disturbances are influenced by a range of demographic and health factors. Importantly, our analysis strongly suggests that a considerable number of Americans suffer from chemosensory disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…12 17–22 Previous studies attempting to address this issue have provided prevalence estimates ranging from 2.7% to 24.5% for smell dysfunction,8–11 13 17 19 20 and 0.6% to 20% for taste dysfunction 1017 20 22 Such variation likely reflects differences in test methods, criteria for defining dysfunction and both sample sizes and sampling procedures, as well as variations in sex, age, health and ethnic composition of the sampled populations.…”
Section: Introductionmentioning
confidence: 99%